Education on the Contextual Utilization of Information Technology Based on the IoT in the Daily Lives of Senior High School Students - Yogyanto, Nurcahyo; Pisriwati, Siti Atwano; Siswanto, Deny Hadi (Indonesian Scientific Publication, 2024)
The implementation of the Internet of Things (IoT) can be applied across various sectors in Indonesia, such as agriculture and healthcare, which demonstrate significant potential for utilizing this technology. To keep pace with technological trends, it is crucial to introduce the concept of IoT early in schools to spark students' interest in this field. This educational program aims to cultivate students' interest in IoT through presentations and live demonstrations using simple IoT-based tools. The event was held at Muhammadiyah Mlati Senior High School on July 27, 2024, involving 30 students. The method used was direct demonstrations of simple IoT tools, supported by effective communication between the educational team and the school. The results showed an improvement in students' understanding of the contextual use of IoT in daily life, with pre-test scores increasing from 53.5 to 78 in the post-test. In conclusion, this program successfully enhanced students' knowledge of IoT, and it is hoped that they will continue to understand its application in solving everyday problems while becoming more skilled in identifying issues and finding solutions using IoT-based technology in the future.